An exploratory study on local moviegoers' reception towards local films in Singapore - Song, Lili (2013)
This exploratory research investigates local moviegoers’ reception towards local films in Singapore. Current statistics regarding the viewership of local films reveal that many indigenous films were not received favourably in terms of box office receipts. It is proposed that the poor box office performance may be related to poor publicity and negative perceptions towards these films.